POTENSI PERTANIAN DAN PERKEBUNAN DI DESA WAISIKA, KECAMATAN ALOR TIMUR LAUT, SEBAGAI SUMBER PENGEMBANGAN EKONOMI MASYARAKAT - Saron Lalangpuling; Vera Marta Kabey; Petrus Mau Tellu Dony; Yermia S. Wabang (JOURNAL OF COMMUNITY DEDICATION, 2026)
Waisika Village, located in the North East Alor District, is an area with significant natural resource potential, particularly in the agricultural and plantation sectors, which serve as the primary source of livelihood for the community. This study aims to describe the diversity of available agricultural and plantation commodities, analyze their utilization levels by the community, and examine their contribution to village economic development. Data were obtained through interviews with village officials and a review of village documents. The results indicate that the most widely cultivated agricultural commodities include rice, corn, beans, vegetables, walnuts, candlenuts, and coconuts. Fertile land conditions, water availability, and traditional farming practices that have been passed down through generations are factors supporting community productivity. Furthermore, plantation commodities such as coconuts, candlenuts, and walnuts have high sales value, potentially becoming superior village products if supported by an adequate marketing system. The agricultural and plantation sectors contribute significantly to food security, family income, and local economic growth. However, this potential has not been optimally utilized. Various obstacles, such as limited transportation access due to damaged roads, a lack of post-harvest innovation and technology, and limited market access, are major challenges to the development of this sector. This research confirms that targeted, modern, and sustainable management of agricultural and plantation potential is crucial for strengthening the economy of Waisika Village and opening up opportunities for developing new businesses based on local natural products.